Clinical characteristics of the first epileptic seizure in children attended at a tertiary hospital in Lima, Peru - Espinoza Quinteros, Ivan Orlando (2025)
Objective: To describe the clinical characteristics, auxiliary tests, and treatment of children presenting with a first epileptic seizure at a Level III-1 national hospital in Lima, Peru. Materials and Methods: A prospective case series study was conducted in patients older than one month and younger than 14 years, treated for a first epileptic seizure at a Level III-1 national hospital in Lima, Peru, between December 2019 and November 2020. The diagnosis of epileptic seizure was established by a pediatric neurologist. The data were collected through interviews with family members and review of medical records. Results: A total of 39 patients were included, with a mean age of 52.6 months. Generalized seizures were the most frequent type (82%), predominantly generalized tonic-clonic seizures (61.5%). The main etiologies were febrile seizures (35.9%), acute central nervous system infections (18%), and traumatic brain injury (12.8%). Upon admission, 46.2% received one or two antiepileptic drugs; at discharge, 33.3% required ongoing medication. Electroencephalograms were performed in 30.8% of patients, computed tomography in 33.3%, and magnetic resonance imaging in 20.5%. Conclusions: Generalized tonic-clonic seizures were the most common type, with febrile seizures, acute CNS infections, and traumatic brain injury as the main etiologies. One-third of patients required medication at hospital discharge.